ANALYSIS OF FINANCIAL STATEMENTS BASED ON PSAK 201 AT PT MUSTIKA RATU Tbk 2018-2022 - Putri, Laura Cahya; Finca, Sabrina Gesila; Uzliawati, Lia (Universitas Nusa Cendana, 2025)
This study aims to analyze the financial statements of PT Mustika Ratu Tbk based on PSAK 201 during the period 2018-2022. The main issues focused on are the financial health of the company through four main aspects: liquidity, solvency, activity, and profitability. The analysis method used is financial ratios, including liquidity, solvency, activity, and profitability ratios. The purpose of this research is to provide a deeper understanding of the company's financial performance during the specified period. The results of the analysis indicate that PT Mustika Ratu Tbk has good liquidity ratios, indicating the company's ability to meet short-term obligations. Additionally, the company's solvency is also considered good, indicating a healthy level of dependence on loans. However, the activity analysis shows less favorable performance in resource utilization and asset management. Nevertheless, the company's profitability is rated as fairly good, indicating its ability to generate profits from its operations. These findings can provide valuable insights for management, investors, and other stakeholders in making better decisions regarding PT Mustika Ratu Tbk. Keywords: PSAK 201; Liquidity Ratio; Solvency Ratio; Activity Ratio; Profitability Ratio